Determinant Entrepreneurship Intention Based on Planned Behavior Theory: A Literature Review - Barreto, Vital Nascimento; Putu Wiagustini, Ni Luh; Rahyuda, Henny; Ketut Sutrisna Dewi, Sayu (Asian Journal of Social and Humanities, 2025)
The purpose of this study is to conduct a thorough literature review to identify the primary factors influencing entrepreneurial intention based on Planned Behavior Theory. By analyzing cognitive, social, and environmental dimensions, this study explores how these elements collectively shape an individual’s intention to pursue entrepreneurship. The review underscores the critical role of self-efficacy, where individuals' belief in their capabilities significantly impacts their entrepreneurial drive. Social influences, such as peer support, cultural norms, and family encouragement, further shape entrepreneurial intentions. Additionally, educational attainment plays a crucial role in providing individuals with the knowledge and skills necessary to identify business opportunities and manage risks effectively. Economic conditions, including market stability and access to funding, also act as external factors that either promote or hinder entrepreneurial pursuits. This study not only consolidates existing research but also identifies gaps in the current literature, particularly the need for cross-cultural studies and deeper analyses of how emerging technologies influence entrepreneurial behavior. The findings contribute to a more nuanced understanding of entrepreneurship intention and provide insights for policymakers, educators, and aspiring entrepreneurs. Future research should focus on longitudinal studies and the impact of evolving economic landscapes to develop more comprehensive strategies that foster entrepreneurship.